ANALISIS HUKUM PERPAJAKAN BAGI INVESTOR INVESTASI PROPERTI - Adie Tirtakusuma; Rimi Gusliana Mais (Bajang Institute, 2024)
Based on Law No. 6 of 1983, which is contained in article 1 paragraph 1, it discusses Tax which in its definition is a contribution that must be paid which is absolute or mandatory and has a value attached to the individual or body with a compelling nature that must be paid to the state based on law. -law, where there is no direct feedback to individuals or bodies when paying, but this is used by the government for the sake of creating social welfare in the country. Tax law, commonly referred to as fiscal law, is a variety of rules to regulate tax collection, so that the people can act as taxpayers and the state plays the role of tax collector. Taxes will be paid from individual or corporate taxpayers which will return to the community but in the form of community prosperity. IAS 40 defines 'investment property' as property (land and/or buildings) owned to obtain rental income. If the lessee owns property based on an operating lease, it will be classified and can be recorded as an investment property and if the property meets the definition then the lessee can use the fair value model for recognized assets